Change in sexual functioning over the menopausal transition: results from the Study of Women's Health Across the Nation. Issue 4 (April 2017) - Avis, Nancy E.; Colvin, Alicia; Karlamangla, Arun S.; Crawford, Sybil; Hess, Rachel; Waetjen, L. Elaine; Brooks, Maria; Tepper, Ping G.; Greendale, Gail A.
Abstract: Objective: The aim of the study was to identify whether there is a decline in sexual functioning related to the menopausal transition or to hysterectomy. Methods: In a cohort of 1, 390 women aged 42 to 52, with intact uterus and at least one ovary, not using hormone therapy, and pre- or early perimenopausal at baseline, we fit piecewise linear growth curves to 5, 798 repeated measurements (seven visits spanning 14.5 y) of a sexual functioning score (range, 5-25) as a function of time relative to date of final menstrual period (FMP) or hysterectomy. Results: Mean sexual functioning at baseline in women with a dateable FMP was 18.0 (SD, 3.4). There was no change in sexual function until 20 months before the FMP. From 20 months before until 1 year after the FMP, sexual function decreased by 0.35 annually (95% CI, −0.44 to −0.26) and continued to decline more than 1 year after the FMP, but at a slower rate (−0.13 annually, 95% CI, −0.17 to −0.10). The decline was smaller in African Americans and larger in Japanese than whites. Vaginal dryness, lubricant use, depressive symptoms, or anxiety did not explain decline in sexual function. Women who had a hysterectomy before the FMP did not show a decline in sexual function before hysterectomy, but scores declined afterward (0.21 annually, 95% CI, −0.28 to −0.14). Conclusions: Decline in sexual function became apparent 20 months before FMP and slowed 1 year after FMP through 5 years afterward. A decline in sexual function was observed immediately after hysterectomy and persisted for the 5 years of observation. Abstract : Supplemental Digital Content is available in the text